South American blastomycosis. Clinical and therapeutic study of 15 new cases - Romero Rivas, Oscar (1961)
Knowledge of the South American Blastomycosis or disease Lutz-Splendore-Almeida, begins with the earliest studies by Lutz in 1905, published in the "Brazil Medical" in 1908, described the clinical aspects of the disease and the morphology of the causal agent placing gender Zymonema. It is from this work that a number of other succeed, but you come to doubt the etiological agent divagándose in their systematic position; S. Fields and F. Almeida (19), (4) report that in 1919 Haberfeld fungus known as Zymonema histoporocellularis, and moreover Fonseca and Leao Area (42), consider the parasite in the genus Coccidioides.